Development of Condition Assessment Criteria for Medium Voltage Underground Cable Water Ingress Joint Using Combined Diagnostic Testing - Anthony T.M.; Mohd Ariffin A.; Sulaiman S.; Nik Ali N.H. (Institute of Electrical and Electronics Engineers Inc., 2024)
In an electric power utility system, medium voltage underground cable joint condition assessment is a crucial part of the network for meeting today's asset management needs. The improperly installed cable joints are exposed to water due to the moist surroundings. Currently, it is challenging to detect the water ingress cable joint in the field. Partial discharge diagnostic testing can locate cable joints with non-conductive defects. However, diagnostic methods such as insulation resistance test and tangent delta test provide bulk information on the overall cable insulation condition. Hence, the network operator is unable to replace the defective cable section. It will be very costly to replace the entire cable as it is across long distances. Time domain reflectometry has been used in the past to determine the length and number of joints in the cable system by analyzing the change of impedance in the pulse reflection. It is proven that the comparison of pulse reflection patterns between all three phases becomes more meaningful by combining it with insulation resistance test and tangent delta test results. The cable joint location selected based on this assessment was retrieved from the field and signs of water ingress were present in the joints. This paper developed condition assessment criteria to detect the defective cable joint that has been affected by water ingress through the combination of diagnostic testing and test result interpretation. 2023 IEEE.